2017
DOI: 10.1371/journal.pone.0171636
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of preoperative IOP reduction using a preservative-free fixed combination of dorzolamide/timolol eye drops versus oral acetazolamide and dexamethasone eye drops and assessment of the clinical outcome of trabeculectomy in glaucoma

Abstract: IntroductionTo demonstrate that preoperative treatment for 28 days with topical dorzolamide/timolol is non-inferior (Δ = 4 mm Hg) to oral acetazolamide and topical dexamethasone (standard therapy) in terms of intraocular pressure (IOP) reduction 3 and 6 months after trabeculectomy in glaucoma patients.Materials and methodsSixty-two eyes undergoing trabeculectomy with mitomycin C were included in this monocentric prospective randomized controlled study. IOP change between baseline and 3 months post-op was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…For bleb filtering and bleb morphology there was overall a trend for increase in bleb score over time (except for DL 2; see Table 5 for details). In line with prior observations for trabeculectomy best corrected visual acuity (BCVA) worsened moderately in all patients at all dose levels for the observation period ( Table 6 ), as described in other trabeculectomy outcome analyses, too [ 27 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…For bleb filtering and bleb morphology there was overall a trend for increase in bleb score over time (except for DL 2; see Table 5 for details). In line with prior observations for trabeculectomy best corrected visual acuity (BCVA) worsened moderately in all patients at all dose levels for the observation period ( Table 6 ), as described in other trabeculectomy outcome analyses, too [ 27 ].…”
Section: Resultssupporting
confidence: 86%
“…Glaucoma continues to be a threat to visual function for millions of patients worldwide. Despite multiple medical treatment options, in the US alone more than 120.000 patients have turned bilaterally blind from glaucoma, representing 1/10 of all cases [ 27 ]. So far, the pathophysiology and underlying molecular mechanisms of glaucoma have not been fully understood [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, dexamethasone, the most potent steroid, was evaluated only in the study of Lorenz et al. (2017), where topical dexamethasone was administrated one week before surgery five times daily. The authors reported a significant IOP increase the day before surgery, with baseline values increasing by 40% (from 19.7 to 27.6 mmHg).…”
Section: Strategies To Prepare the Ocular Surface For Filtration Surgerymentioning
confidence: 99%
“…In a recent 24-h investigation it has been shown that the IOP-lowering effect of PF DTFC administered twice daily is additive to that of PF tafluprost administered once in the evening [ 40 ]. Finally, PF DTFC has been successfully tried for controlling IOP for 3 months temporizing before planned glaucoma filtration surgery, an intervention for which the preservative related ocular irritation may have a negative effect on surgical success [ 43 ].…”
Section: Looking Towards the Future: Pf Dtfcmentioning
confidence: 99%